النموذج السببي للعلاقة بين المخططات المعرفية اللاتكيفية المبكرة وأساليب التعلق وأعراض اضطراب الشخصية التجنبية لدى طلاب الجامعة - الحديبي، مصطفى عبدالمحسن عبدالتواب; الدواش، فؤاد محمد حسن إسماعيل (جامعة الفيوم - كلية التربية, 2020)
هدف البحث الحالي إلى التحقق من صحة النموذج البنائي للعلاقات السببية بين المخططات المعرفية اللاتكيفية المبكرة وأساليب التعلق واضطراب الشخصية التجنبية لدى طلاب الجامعة؛ للتوصل إلى نموذج يحدد الآثار المباشرة وغير المباشرة بين تلك المتغيرات في ضوء ما تعكسه بيانات الدراسة، والكشف عن أكثر هذه المخططات انتشارا لدى ذوي اضطراب الشخصية التجنبية، ومدى تمايز تلك المخططات بتباين أساليب التعلق، وبلغ قوام الدراسة الاستطلاعية 130 طالبا وطالبة من طلاب الجامعة؛ للتحقق من كفاءة أدوات الدراسة، في حين بلغ عدد أفراد الدراسة الأساسية 495 طالبا وطالبة، بعد استبعاد حالات عدم الجدية في الأداء على أدوات الدراسة المتمثلة في: مقياس المخططات المعرفية اللاتكيفية المبكرة (النسخة المختصرة) "ليونج" تعريب وتقنين محمد السيد عبد الرحمن، محمد أحمد إبراهيم سعفان (2014)، ومقياس اضطراب الشخصية التجنبية (عبد الرقيب أحمد البحيري وآخرون، 2020)، ومقياس أساليب التعلق إعداد الباحثان، وأسفرت نتائج الدراسة عن تباين المشاركين بالدراسة في تبني المخططات المعرفية اللاتكيفية المبكرة طبقا لأساليب التعلق، ووجود فروق دالة إحصائيا بين متوسطي درجات مرتفعي ومنخفضي اضطراب الشخصية التجنبية على مقياس المخططات المعرفية اللاتكيفية المبكرة، لصالح مرتفعي اضطراب الشخصية التجنبية، ما عدا مخطط التضحية بالذات، حيث أظهرت النتائج عدم وجود فروق بين مرتفعي ومنخفضي اضطراب الشخصية التجنبية به، كما أظهرت نتائج تحليل المسار مؤشرات حسن مطابقة للنموذج المقترح، حيث بلغت قيمة مؤشر كا2 ” Chi- Square(215.57) ومؤشر حسن المطابقة GFI (0.972) ومؤشر حسن المطابقة المصحح AGFI (0.911)، ومؤشر المطابقة المعياري NFI (0.895)، ومؤشر المطابقة المقارن CFI (0.874)، ومؤشر المطابقة النسبي RFI (0.869)، ومؤشر المطابقة التزايدي IFI (0.972)، ومؤشر جذر متوسط مربع خطأ الاقتراب RMSEA (0.066)؛ مما يشير إلى تطابق النموذج المقترح مع بيانات الدراسة الحالية، وتم تفسير النتائج في ضوء الأدبيات النظرية لمتغيرات الدراسة والدراسات ذات الصلة، وبالاعتماد على هذه النتائج وتفسيرها تم صياغة عدد من التوصيات.
The current research aimed to validate the structural model of causal relationships between early maladaptive cognitive schemes and the attachment styles and avoidant personality disorder among university students; to come up with a model that defines the direct and indirect effects of these variables in the light of what the study data reflects, and to uncover the most prevalent plans among those with an avoidant personality disorder, and the extent of the differentiation of these plans in the attachment styles. The surveyed study has a population of 130 university students (males and females) to verify the efficiency of study tools, The number of students in the basic study was 495, after the exclusion of the unserious performance students on the tools of the study: The scale of the cognitive schematics was used in the short form. "Leung" translated and codified by Mohamed Al-Sayyed Abdurrahman, Mohammed Ahmed Ibrahim Saafan (2014), the measurement of avoidant personality disorder (Abdul Raqib Ahmed Al-Buhairi et al , 2020), and the measurement of attachment styles. -Prepared by the researchers-. The study resulted that the participants are different in adopting the early maladaptive schemes according to the attachment styles. And there are statistically significant differences between the score average of high and low avoidant personality disorder on the early maladaptive cognitive schemes scale, in favor of those with high avoidance personality disorder, except for the self-sacrifice scheme, and there are no differences between the high and low avoidant personality disorder on it. The results of the trajectory analysis also showed indicators of good conformity to the proposed model, as the value of Chi-Square Index (215.57), GFI Goodness of Fit Index (0.972), Adjusted Goodness of Fit Index (0.911), NFI Normed Fit Index (0.895), and Comparative Fit Index CFI (0.874), RFI Relative Fit Index (0.869), IFI Incremental Fit Index (0.972), RMSEA (0.066); This indicates that the proposed model matches the data of the current study, and the results were interpreted in light of the theoretical literature of the study variables and related studies, and based on these results and their interpretation, a number of recommendations were formulated.
Keywords: المخططات المعرفية -- الاضطرابات النفسية -- الشخصية التجنبية -- طلبة الجامعات